CASE STUDY ON CORRELATION OF WORKPLACE FRIENDSHIP WITH VALUE CO-CREATION - Shen, Ya-Chi; Lin, Chin-Chiuan (Graduate Program of Universitas Tarumanagara, 2025)
In the rapid changing competitive environment, attracting cooperative companies to maximize profits and create a win-win situation highlights the value of workplace friendship in corporate partnerships. The present study investigate how the two enterprise (S power plant and the contractor company C) can overcome the differences and achieve value co-creation goal due to improvement the workplace friendship despite the differences in corporate culture, business cognition and practical operation understanding?. In the present study, the in-depth interview was conducted to the management personnel of S power plant, the contact responsible person of company C, and contracted labour personnel. Two research conclusions were obtained: (1) Personnel recruitment serves as a channel for dialogue, initiating value co-creation for both parties; (2) Only when both parties jointly create centripetal force, cohesion, and reputation can they jointly value co-creation. The suggestions are also made respectively to human resources management of S power plant based on research practice observations.